Advances in industrial and labor relations. Volume 18 - Lewin, David, 1943-; Kaufman, Bruce E.; Gollan, Paul J. (Emerald, 2011)
This volume contains seven distinctive papers that explore important aspects of contemporary employment relationships. Some of the papers are more micro level in orientation, whereas others are more macro oriented. Some papers contain extensive quantitative analysis, while others feature deep qualitative analysis. Some of the papers contain evidence and examples from the USA, whereas others contain evidence and examples from the UK, Canada, and the Netherlands. As a set, these papers are in keeping with the traditions of AILR which are to offer global perspectives on employment relationships, draw knowledge from wherever it is forthcoming and relevant, represent a mix of disciplinary perspectives, and encourage authors to pursue their topics more deeply than might be afforded by other journals and publication outlets. In particular, the papers in Volume 18 of AILR deal with the dual alignment of industrial relations activity in terms of strategic choice and mutual gains; evidence from Canada about first contract arbitration and its implications for the proposed USA Employee Free Choice Act; the search for an integrated model of worker participation and organizational performance at the level of the firm; the impact of employee well-being policies and sickness absence on workplace performance; the role of participation in decision making in reducing work-life conflict; an institutional analysis of union engagement in Western New York State economic development; and the International Labor Organizations enforcement of labor standards in the global maritime industry. The authors of these papers have invested considerable effort in conducting the type and depth of analysis that sheds new light on their chosen topics, and the Editors are pleased to publish the results of their work in this volume.
Keywords: Business & Economics -- General.; Economics.; Economic theory & philosophy.; Industrial relations.; elektronické knihy; electronic books